Comparison of weather element values from power project and observation data, a case study of southern east coast region of Thailand - Phumkokrux Nutthakarn; Malee Nurkasma; Pattanasak Patiya; Yodying Aphittha (Glasnik Srpskog Geografskog Društva, 2025)
Weather elements monitoring is important for all activities planning, which were: Air Pressure (Press.), Maximum (TMax) and Minimum (TMin) Temperature, Relative Humidity (%RH), Rainfall (Pr.), Wind Speed (WS) and Wind Direction (WD) leading to the objectives which are 1) to compare the observation data from 15 stations over the Southern East coast region of Thailand and POWER Project data in the same locations using MAE methods to confirm the suitability of using as alternative data and 2) to study each element characteristics in the study area using kriging technique and its trend by Man-Kandal trend test and Sen’s slope method. The results indicated that TMax, TMin, Pr., %RH, Press, and WS data from the POWER Project could be used instead of observation data after these values were adapted following MAE values. However, WD data from the POWER Project were not appropriate to use instead of observation data. The big increasing trends were found at high latitude for TMin and %RH while these were found at low latitude for TMax and Pr.